ARCHIPELAGO : Oleh-oleh dari Solo [rekaman video] / penanggung jawab Andy F Noya ; editor Syofie Velveta, Anddy C. - Andy F Noya; Syofie Velveta; Anddy C. (Metro TV, 2007)
DVD digital, stereo 4 3/4 in